The Effect of Bay Leaf Decoction on Blood Decrease Uric Acid Levels in the Elderly - Nurhafni Nurhafni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Gout is a type of inflammatory joint disease that occurs due to the accumulation of uric acid crystals. It usually occurs in several joints, such as the toes, ankles, knees, and big toes. Gout is also commonly called gout. This study aims to determine the Effect of Bay Leaf Decoction on Reducing Uric Acid in the Elderly at the Binjai Estate Health Center in 2024. The design of this study uses a descriptive correlation research method ( correlation study). The population in this study were all elderly people as many as 26 respondents, a total sampling of 26 samples. The variables in the study were the independent variable, namely boiled bay leaves and the dependent variable, uric acid levels in the elderly. The research instrument used a questionnaire and chi-square test. The results of the study show that regular elderly drink stew leaf greetings , grade sour tendon down as many as 16 people (84.2%) and elderly minority drink stew leaf regards regular , level sour tendon No down as many as 3 respondents (15.8%) while majority elderly who do not regular drink stew leaf greetings , grade sour tendon down as many as 1 respondent (14.2%) and a minority elderly who do not regular drink leaf greetings , grade sour tendon No down as many as 6 respondents (85.8%). The chi-square test shows that mark significant p-Value = 0.002< a( 0.05), so H 1 is accepted. Conclusion This research is There is connection influence stew leaf regards to decline level sour veins in the elderly at the Community Health Center Binjai Estate.